Echocardiography of Right Ventriculoarterial Coupling Combined With Cardiopulmonary Exercise Testing to Predict Outcome in Heart Failure - Guazzi, Marco; Naeije, Robert; Arena, Ross; Corrà, Ugo; Ghio, Stefano; Forfia, Paul; Rossi, Andrea; Cahalin, Lawrence P; Bandera, Francesco; Temporelli, Pierluigi (Chest, 2015)
Pulmonary hypertension, which is related to right ventricular (RV) failure, indicates a poor prognosis in heart failure (HF). Increased ventilatory response and exercise oscillatory ventilation (EOV) also have a negative impact. We hypothesized that the severity classification of HF and risk prediction could be improved by combining functional capacity with cardiopulmonary exercise testing (CPET) and RV-pulmonary circulation coupling, as evaluated by the tricuspid annular plane systolic excursion (TAPSE)-pulmonary artery systolic pressure (PASP) relationship. Four hundred fifty-nine patients with HF were assessed with Doppler echocardiography and CPET and were tracked for outcome. The subjects were followed for major cardiac events (cardiac mortality, left ventricular assist device implant, or heart transplant). Cox regression and Kaplan-Meier analyses were performed with TAPSE and PASP as individual measures that were then combined into a ratio form. The TAPSE/PASP ratio (TAPSE/PASP) was the strongest predictor, whereas the New York Heart Association classification and EOV added predictive value. A four-quadrant group prediction risk was created based on TAPSE (< 16 mm or ≥ 16 mm) vs PASP (< 40 mm Hg or ≥ 40 mm Hg) thresholds and the CPET variables distribution as follows: group A (TAPSE > 16 mm and PASP < 40 mm Hg) presented the lowest risk (hazard ratio, 0.17) and best ventilation; group B exhibited a low risk (hazard ratio, 0.88) with depressed TAPSE (< 16 mm) and normal PASP, a preserved peak oxygen consumption (V.o2), but high ventilation. Group C had an increased risk (hazard ratio, 1.3; TAPSE ≥ 16 mm, PASP ≥ 40 mm Hg), a reduced peak V.o2, and a high EOV prevalence. Group D had the highest risk (hazard ratio, 5.6), the worse RV-pulmonary pressure coupling (TAPSE < 16 and PASP ≥ 40 mm Hg), the lowest peak V.o2, and the highest EOV rate. TAPSE/PASP, combined with exercise ventilation, provides relevant clinical and prognostic insights into HF. A low TAPSE/PASP with EOV identifies patients at a particularly high risk of cardiac events.